Meningkatkan Kualitas Pendidikan pada SDM Tenaga Pendidik - Oki Iqbal Khair; Diana Harjayanti; Ambar Widya Lestari (Lembaga Kajian Demokrasi dan Pemberdayaan Masyarakat (LKD-PM), 2022)
The main problem faced in implementing a good education pattern is digital development which is increasingly fast today and affects every line of life, including the world of education. Through community service activities carried out by lecturers of Pamulang University, the Management study program is expected to provide direct benefits to the community in the environment the Al-Mukhlishin Cares Community Foundation, Pesona Pamulang Housing, RT 002 RW 15, Pondok Petir Village, Bojongsari District, Depok, West Java 16517. The implementation of this community service activity is an effort to produce a smart and quality community through good parenting and education, through improving the quality of education because this is very much needed by a nation that wants to advance because quality education can support development in all fields.